Spanish Consortium for Ageing Normative Data (SCAND): Screening Tests (MMSE, GDS-15 and MFE) - Delgado-Losada, María; López-Higes, Ramón; Rubio-Valdehita, Susana; Facal, David; Lojo-Seoane, Cristina; Montenegro-Peña, Mercedes; Frades-Payo, Belén; Fernández-Blázquez, Miguel (Psicothema, 2021)
Detecting cognitive impairment is a priority for health systems. The aim of this study is to create normative data on screening tests (MMSE, GDS and MFE) for middle-aged and older Spanish adults, considering the effects of sociodemographic factors. A total of 2,030 cognitively intact subjects who lived in the community, aged from 50 to 88 years old, participated voluntarily in SCAND consortium studies. The statistical procedure included the conversion of percentile ranges into scalar scores. Secondly, the effects of age, educational level and gender were verified. Linear regressions were used to calculate the scalar adjusted scores. Cut-off values for each test were also calculated. Scalar scores and percentiles corresponding to MMSE, GDS-15 and MFE are shown. An additional table is provided which shows the points that must be added or subtracted from MMSE score depending on the subject's educational level. The current norms should provide clinically useful data for evaluating Spanish people aged 50 to 88 years old and should contribute to improving the detection of initial symptoms of cognitive impairment in people living in the community, taking into account the influence of gender, age and educational level.